A copper-based bimetallic catalyst, its preparation method and use

CN118162145BActive Publication Date: 2026-10-23FUZHOU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410391135.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-02
Publication Date
2026-10-23
Estimated Expiration
2044-04-02

AI Technical Summary

Technical Problem

如专利《一种用于选择性催化氧化NH3的贵金属-过渡金属复合催化剂的制备方法及应用》(申请号202211216578.1)公开了了一种贵金属-过渡金属催化剂,在230℃的温度下实现氨的完全转化,但其使用了贵金属成本高

Benefits of technology

[0021](1)本发明所制备的铜基双金属催化剂氨选择性氧化催化剂方法可一步热解完成,具有步骤简单易行、快捷高效和成本低廉的特点;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application relates to a preparation method and application of a copper-based bimetallic catalyst for selective oxidation of ammonia, which utilizes the complexation of organic acid and amine with metal ions in an aqueous solution, forms a wet gel with water evaporation, removes water from the wet gel through drying to obtain a dry gel, and obtains the copper-based bimetallic ammonia oxidation catalyst after high-temperature calcination treatment of the dry gel. The synthesis technical route is simple and efficient, no organic solvent is needed in the preparation process, no pollution is generated, the preparation period is short, and green and rapid preparation of the material can be realized. The copper-based bimetallic ammonia selective oxidation catalyst prepared in the application contains highly dispersed, easily reduced copper oxide species, rich Cu + And oxygen vacancies, and rich acid sites. In the selective oxidation of ammonia, excellent catalytic performance is shown, which is superior to the currently commonly used ammonia selective oxidation catalysts, such as Pt / gamma-Al2O3, copper-based and iron-based molecular sieves, etc. It can be used as a candidate material for industrial application of low-temperature selective oxidation of ammonia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical fields:

[0001] This invention belongs to the field of inorganic material preparation and application, specifically relating to a method for preparing and applying a copper-based bimetallic catalyst for the selective oxidation of ammonia. Background technology:

[0002] Large-scale anthropogenic ammonia emissions have a series of adverse environmental impacts. For example, atmospheric ammonia is a major alkaline component involved in the nucleation of secondary aerosols. With the rapid development of industry and the rapid increase in the number of motor vehicles in recent years, ammonia emissions from industry (stationary sources) and motor vehicles (mobile sources) have also been increasing year by year. Ammonia emissions from stationary and mobile sources mainly come from two aspects: first, ammonia escape caused by various factories that produce and use ammonia; and second, NH3 escape caused by the ammonia selective catalytic reduction (NH3-SCR) module in stationary exhaust / diesel vehicle exhaust aftertreatment systems, or ammonia generated on the three-way catalyst of gasoline vehicles. Currently, there are various methods reported in the literature for controlling and treating ammonia emissions, mainly including absorption decomposition, microbial methods, catalytic decomposition, and catalytic combustion (oxidation). Considering the treatment cost, degradation efficiency, and actual working conditions, the NH3 catalytic combustion (oxidation) method is considered to be the most suitable treatment process for ammonia escape from both stationary and mobile vehicle exhaust sources. Because the target products of ammonia catalytic oxidation in the field of vehicle exhaust treatment are generally nitrogen and water, catalytic combustion (oxidation) methods in this field typically refer to the selective catalytic oxidation of NH3 (NH3-SCO). However, this technology also has some problems; the reaction products include byproducts such as N2O, NO, and NO2, which can pose significant risks to human health and the ecological environment. Therefore, the key technical issues that this technology needs to address are: improving the conversion rate of NH3 under low-temperature conditions, increasing the selectivity of N2, and reducing the generation of byproducts.

[0003] To date, various catalytic materials have been studied for the NH3-SCO reaction, mainly including three categories: noble metal catalysts (Pt, Ru, Ir, Au, and Rh), modified molecular sieve catalysts, and transition metal oxide catalysts. Catalysts composed of platinum supported on metal oxides (such as γ-alumina) are the most active known catalysts for the selective oxidation of ammonia, exhibiting an ignition temperature of NH3 below 250°C. They are very effective at removing NH3 from the gas stream under oxidizing conditions. For example, the patent "Preparation Method and Application of a Noble Metal-Transition Metal Composite Catalyst for the Selective Catalytic Oxidation of NH3" (application number 202211216578.1) discloses a noble metal-transition metal catalyst that achieves complete ammonia conversion at a temperature of 230°C, but it uses noble metals, resulting in high costs. For example, the invention patent "A Cu-Ce Catalyst with Nanorod Structure for NH3 Catalytic Oxidation, Preparation Method and Application" (application number 201810337489.X) discloses a Cu-Ce catalyst with a nanorod structure, a preparation method and its application in the selective catalytic oxidation of ammonia. This catalyst exhibits a good morphology effect to enhance the catalytic oxidation activity of NH3; however, the preparation conditions are harsh and the steps are complex. The invention patent "NH3-SCO Catalyst for Diesel Vehicle Exhaust Gas and Preparation Method" (application number 201911205878.8) discloses a preparation method for an NH3-SCO catalyst for diesel vehicle exhaust gas, characterized by including: Cu salt and Co salt as active components, and dried Beta molecular sieve as a support; however, the Co element in this patent is highly toxic and easily causes secondary pollution, and the cost of the Beta molecular sieve is high.

[0004] In supported copper-based catalysts, Cu is the dominant element. + and Cu 2+ The catalyst exists in the form of a support, and these catalysts are in a reducing atmosphere (NH3), with some Cu... 2+ Easily reduced to Cu + And Cu + It is easily oxidized to Cu in oxidizing atmospheres (NO and O2). 2+ The reduction process leads to the loss of lattice oxygen, thus significantly increasing the number of oxygen vacancies on CuxOy. When these oxygen vacancies adsorb O2 from the reactant gas, it causes Cu... 2+ The formation of superoxides; the continuous formation of superoxides leads to the adsorption and desorption of O2, causing O2 to switch between adsorbed oxygen and lattice oxygen. Therefore, Cu x O y It possesses a high oxygen storage capacity. This results in high NH3-SCO activity in the transition metal copper. Furthermore, the superoxide species in CuO have a stronger adsorption capacity for NH3 than the lattice oxygen or surface oxygen in CuO, making it an active center for NH3-SCO at low temperatures.

[0005] The mechanism of action of CexOy species is similar to that of CuxOy, in Ce 3+ With Ce 4+ In the redox process, CeO2 superoxide can be generated, which improves the oxidation activity of NH3. However, Ce is rarely used as a single active metal to be loaded onto other supports because CeO2 has low redox capacity and NH3 adsorption capacity. In addition, CeOy species themselves do not have strong acid sites to adsorb NH3, which also leads to the unsatisfactory catalytic activity of pure CeOy species for NH3; however, CeOy itself has a strong O adsorption capacity and can be loaded or combined with other metal oxides to form highly active NH3-SCO catalysts. Based on this, this patent proposes a green and simple method to synthesize a CuO / CeO2 bimetallic ammonia selective oxidation catalyst. Using the sol-gel method, with copper salts and cerium salts as precursors, organic acids as chelating agents, and organic amines as reducing agents and chelating agents, the CuO / CeO2 bimetallic ammonia selective oxidation catalyst was prepared. The CuO / CeO2 catalyst prepared by this method has excellent low-temperature activity and nitrogen selectivity. Summary of the Invention:

[0006] This invention overcomes the shortcomings of low-temperature activity in copper-based selective oxidation of ammonia and provides a method for preparing a copper-based bimetallic catalyst for selective oxidation of ammonia. The method uses organic acids and amines with copper and cerium salts as raw materials, mixes them evenly in a solution and further performs gelation treatment, and finally calcines them at high temperature in a muffle furnace to obtain a copper-based bimetallic selective oxidation catalyst for ammonia. The preparation method is simple and easy to operate, uses green and environmentally friendly raw materials, is low in cost, and does not produce toxic substances during the preparation process.

[0007] To achieve the above objectives, the technical solution of the present invention is as follows:

[0008] A method for preparing a copper-based bimetallic catalyst for the selective oxidation of ammonia includes the following steps:

[0009] Step (1) Use water as a solvent to prepare a metal salt solution of a certain proportion, disperse it by ultrasonic vibration, and heat it to a certain temperature;

[0010] Step (2) Dissolve a certain mass of organic acid in a certain volume of deionized water, then add a certain volume of organic amine dropwise into the organic acid solution to form a mixed solution, and then add it to the metal salt solution.

[0011] After mixing in step (3), stir for a period of time to form a gel, let it stand, and then dry it at a certain temperature for a period of time to obtain a dry gel;

[0012] Step (4) involves calcining the dry gel in air at a certain heating rate to obtain a copper-based bimetallic ammonia selective oxidation catalyst.

[0013] Further, the volume of the solvent water in step (1) is 40-100 mL, and the metal salt used includes at least one of copper nitrate, copper sulfate, and copper acetate, and at least one of cerium nitrate, cerium sulfate, and cerium acetate; the molar ratio of copper salt to cerium salt is 5:95 to 95:5.

[0014] Further, the ultrasonic dispersion time in step (1) is 30-60 min, the ultrasonic frequency is 33-80 kHz, and the heating temperature is 60-80 °C.

[0015] Further, in step (2), the organic acid includes at least one of oxalic acid, citric acid, glycine, and tartaric acid; the organic amine includes at least one of ethylenediamine, aniline, and hexamethylenetetramine; the molar ratio of the metal salt to the organic acid is 1:1 to 1:3; and the molar ratio of the organic acid to the amine is 1:2 to 1:3.

[0016] Furthermore, the stirring time in step (3) is 2 to 4 hours, and the settling time is 1 to 20 hours.

[0017] Furthermore, the drying temperature of the dry gel in step (3) is 60-80℃, and the drying time is 12-24h.

[0018] Further, the heating rate in step (4) is 2-5℃ / min, the calcination temperature is 400-600℃, and the calcination time is 4-6h.

[0019] The aforementioned copper-based bimetallic catalyst for selective oxidation of ammonia specifically refers to: using NH3 as the raw material gas, a copper-based bimetallic catalyst for selective oxidation of ammonia as the catalyst, and performing selective oxidation of NH3.

[0020] The advantages of this invention are:

[0021] (1) The copper-based bimetallic catalyst for selective oxidation of ammonia prepared by the present invention can be completed in one step by pyrolysis, and has the characteristics of simple and easy steps, fast and efficient and low cost.

[0022] (2) This invention contains no toxic solvents and is environmentally friendly;

[0023] (3) The copper-based bimetallic catalyst for ammonia selective oxidation prepared in this invention exhibits highly dispersed, easily reducible copper oxide species, a high content of monovalent copper species, abundant oxygen vacancies, and surface acidic sites. It achieves a conversion rate of up to 100% and a nitrogen selectivity of over 90% at a temperature of 220°C. Attached image description:

[0024] Figure 1 XRD patterns of copper-based bimetallic ammonia selective oxidation catalysts prepared in Examples 1-4;

[0025] Figure 2 The above are H2-TPR diagrams of the catalysts prepared in Examples 1-4 of this invention.

[0026] Figure 3 The above are Cu2p XPS diagrams of the catalysts prepared in Examples 1-4 of this invention.

[0027] Figure 4 The above are O1s XPS diagrams of the catalysts prepared in Examples 1-4 of this invention.

[0028] Figure 5 The NH3-TPD diagrams are of the catalysts prepared in Examples 1-4 of this invention.

[0029] Figure 6 The activity diagrams are of the catalysts prepared in Examples 1-4 of this invention.

[0030] Figure 7 This is a nitrogen selectivity diagram of the catalysts prepared in Examples 1 to 4 of the present invention. Specific implementation methods:

[0031] The specific implementation methods of the present invention will be described in detail below. The specific implementation methods described herein are for illustration and explanation only and are not intended to limit the present invention.

[0032] Example 1: 0.12 g of copper nitrate trihydrate and 4.12 g of cerium nitrate hexahydrate were weighed and dissolved in 20 mL of deionized water. The solutions were ultrasonically dispersed at room temperature for 30 min to form a homogeneous phase. 3.15 g of citric acid monohydrate was weighed and dissolved in 20 mL of deionized water. The solutions were stirred at room temperature to form a homogeneous phase. Then, 2 mL of ethylenediamine was added dropwise to the citric acid solution for later use. The mixed solution of copper nitrate and cerium nitrate was transferred to a water bath and heated to 80 °C. At 80 °C, the mixed solution of ethylenediamine and citric acid was added dropwise to the mixed solution of copper nitrate and cerium nitrate, and the mixture was heated in the water bath for 4 h. After gel formation, the mixture was allowed to stand at room temperature for 2 h, then placed in an oven and dried at 80 °C for 12 h. The resulting dry gel was calcined in air at 400 °C for 4 h and designated as catalyst Cu5Ce95.

[0033] Example 2: 0.24 g of copper nitrate trihydrate and 3.91 g of cerium nitrate hexahydrate were weighed and dissolved in 20 mL of deionized water. The solutions were ultrasonically dispersed at room temperature for 30 min to form a homogeneous phase. 3.15 g of citric acid monohydrate was weighed and dissolved in 20 mL of deionized water. The solutions were stirred at room temperature to form a homogeneous phase. Then, 2 mL of ethylenediamine was added dropwise to the citric acid solution for later use. The mixed solution of copper nitrate and cerium nitrate was transferred to a water bath and heated to 80 °C. At 80 °C, the mixed solution of ethylenediamine and citric acid was added dropwise to the mixed solution of copper nitrate and cerium nitrate, and the water bath was heated for 4 h. After gel formation, the solution was allowed to stand at room temperature for 2 h, then placed in an oven and dried at 80 °C for 12 h. The resulting dry gel was calcined in air at 400 °C for 4 h and designated as catalyst Cu10Ce90.

[0034] Example 3: 0.36 g of copper nitrate trihydrate and 3.69 g of cerium nitrate hexahydrate were weighed and dissolved in 20 mL of deionized water. The solutions were ultrasonically dispersed at room temperature for 30 min to form a homogeneous phase. 3.15 g of citric acid monohydrate was weighed and dissolved in 20 mL of deionized water. The solutions were stirred at room temperature to form a homogeneous phase. Then, 2 mL of ethylenediamine was added dropwise to the citric acid solution for later use. The mixed solution of copper nitrate and cerium nitrate was transferred to a water bath and heated to 80 °C. At 80 °C, the mixed solution of ethylenediamine and citric acid was added dropwise to the mixed solution of copper nitrate and cerium nitrate, and the mixture was heated in the water bath for 4 h. After gel formation, the mixture was allowed to stand at room temperature for 2 h, then placed in an oven and dried at 80 °C for 12 h. The resulting dry gel was calcined in air at 400 °C for 4 h and designated as catalyst Cu15Ce85.

[0035] Example 4: 0.48 g of copper nitrate trihydrate and 3.47 g of cerium nitrate hexahydrate were weighed and dissolved in 20 mL of deionized water. The solutions were ultrasonically dispersed at room temperature for 30 min to form a homogeneous phase. 3.15 g of citric acid monohydrate was weighed and dissolved in 20 mL of deionized water. The solutions were stirred at room temperature to form a homogeneous phase. Then, 2 mL of ethylenediamine was added dropwise to the citric acid solution for later use. The mixed solution of copper nitrate and cerium nitrate was transferred to a water bath and heated to 80 °C. At 80 °C, the mixed solution of ethylenediamine and citric acid was added dropwise to the mixed solution of copper nitrate and cerium nitrate, and the mixture was heated in the water bath for 4 h. After gel formation, the mixture was allowed to stand at room temperature for 2 h, then placed in an oven and dried at 80 °C for 12 h. The resulting dry gel was calcined in air at 400 °C for 4 h and designated as catalyst Cu2OCe80.

[0036] The copper-based bimetallic ammonia selective oxidation catalysts with different loadings were analyzed and tested accordingly:

[0037] Figure 1The XRD patterns of copper-based bimetallic ammonia selective oxidation catalysts with different loadings are shown. All four samples showed only characteristic diffraction peaks of CeO2, and no CuO crystal phase was found, indicating that CuO is highly dispersed on CeO2.

[0038] Figure 2 The figures show the H2-TPR curves for Examples 1-4 of this invention. The figures show that as the copper loading increases, the reduction peak of copper oxide decreases, with the reduction peak centers at 110℃ and 160℃, indicating that copper oxide is very easily reduced in these samples. The copper-based bimetallic ammonia selective oxidation catalyst exhibits superior redox performance.

[0039] Figure 3 The figures show the Cu2p XPS curves for Examples 1-4 of this invention. The figures show that Examples 1-4 have abundant Cu. + Ions, Cu 2+ / Cu + Ion cycling is beneficial for the adsorption of ammonia and electron transfer.

[0040] Figure 4 The figures show the O1s XPS curves for Examples 1-4 of this invention. The figures show that Examples 1-4 have a relatively high proportion of adsorbed oxygen and abundant oxygen vacancies, which is beneficial for oxygen adsorption and activation.

[0041] Figure 5 The figures show the NH3-TPD curves for Examples 1-4 of this invention. The figures show that Examples 1-4 possess abundant acidic sites, which is beneficial for the adsorption and activation of ammonia.

[0042] Figure 6 The selective oxidation performance of ammonia by a copper-based bimetallic ammonia selective oxidation catalyst was tested under the following conditions: catalyst dosage was 0.1 g, gas composition was 3000 ppm NH3, 2.5% O2, and Ar was used as the equilibrium gas. The reaction space velocity was 60000 h⁻¹. -1 .

[0043] Figure 7 The selective oxidation of ammonia by nitrogen using a copper-based bimetallic ammonia catalyst was studied under the following conditions: catalyst dosage was 0.1 g, gas composition was 3000 ppm NH3, 2.5% O2, and Ar was used as the equilibrium gas. The reaction space velocity was 60000 h⁻¹. -1 .

[0044]

[0045] Table 1 shows the complete conversion temperature and selectivity of ammonia in Examples 1-4.

[0046] In the examples, copper-based bimetallic ammonia selective oxidation catalysts with different copper loadings were used, among which the low-temperature activity and selectivity of catalyst Cu20Ce80 were superior to those of other samples and commercial platinum-aluminum catalysts.

[0047] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.

Claims

1. The application of copper-based bimetallic catalysts in the selective oxidation of ammonia, characterized by: The application temperature is 220℃, during which ammonia is selectively oxidized to N2; The preparation method of the copper-based bimetallic catalyst includes the following steps: Step (1) Use water as a solvent to prepare a metal salt solution of a certain proportion, disperse it by ultrasonic vibration, and heat it to a certain temperature; Step (2) Dissolve a certain mass of organic acid in a certain volume of deionized water, then add a certain volume of organic amine dropwise into the organic acid solution to form a mixed solution, and then add it to the metal salt solution. After mixing in step (3), stir for a period of time to form a gel, let it stand, and then dry it at a certain temperature for a period of time to obtain a dry gel; Step (4) The dry gel is calcined in air at a certain heating rate to obtain a copper-based bimetallic ammonia selective oxidation catalyst. In step (1), the volume of water is 40-100 mL, and the metal salts used include at least one of copper nitrate, copper sulfate, and copper acetate, and at least one of cerium nitrate, cerium sulfate, and cerium acetate; the molar ratio of copper salt to cerium salt is 5:95~95:

5. Step (2) Organic acids include at least one of oxalic acid, citric acid, glycine, and tartaric acid; organic amines include at least one of ethylenediamine, aniline, and hexamethylenetetramine; the molar ratio of metal salt to organic acid is 1:1 to 1:3; the molar ratio of organic acid to amine is 1:2 to 1:

3. The heating rate in step (4) is 2~5 ℃ / min, the calcination temperature is 400~600 ℃, and the calcination time is 4~6 h.

2. The application according to claim 1, characterized in that: In step (1), the ultrasonic oscillation time is 30-60 min, the ultrasonic frequency is 33-80 kHz, and the heating temperature is 60-80 ℃.

3. The application according to claim 1, characterized in that: The stirring time in step (3) is 2-4 hours, and the standing time is 1-20 hours.

4. The application according to claim 1, characterized in that: In step (3), the drying temperature is 60~80 ℃ and the drying time is 12~24 h.

Citation Information

Patent Citations

  • Cu-Ce catalyst of nanometer rod-shaped structure for NH3 catalytic oxidation as well as preparation method and application thereof

    CN108514881A

  • NH3-SCO catalyst for diesel vehicle exhaust and its preparation method

    CN111068764B

  • Preparation method and application of noble metal-transition metal composite catalyst for selective catalytic oxidation of NH3

    CN115445614A

  • Method of producing a porous crystalline material with a highly uniform structure

    CN108883389A